THE ROLE OF INTERNATIONAL COMMERCIAL ARBITRATION IN ENHANCING FOREIGN DIRECT INVESTMENT: LESSONS FOR ALGERIA: FDI Arbitration in Algeria (UUM Journal of Legal Studies, 2020)
Following the upsurge and development in the globalized and emerging economies, commercial misunderstanding and disputes transcending national borders may also be on the rise. Such disputes can hamper the economic activities and operation within those emerging economies, in particular those activities related to the foreign direct investment. National legal mechanism may not be attractive to international investors. Instead, international commercial arbitration (ICA) could be a preferred choice by foreign investors through which contractual disputes can be resolved via independent forum because it helps to foster market efficiency, facilitate foreign direct investment and protect the interest of foreign investors. To offer insights on this issue theoretically and empirically, this paper presents a logic-based and empirically based conceptual discussion to investigate the influence of ICA on FDI, in particular its application in the context of Algeria and the importance of domestic courts’ execution of arbitral awards. The paper finds that ICA is indispensable to contractual conflict resolution and can consequently assists FDI inflows into the country that entrenches it. Algeria may increase FDI inflows by strengthening the legal framework for arbitration through the enhancement of national laws relating to ICA and guaranteeing their effective execution and enforcement by local judicial system.